UMP Collaborates with Bank Rakyat to offer i-Education Financing - UMP, PNC (2018)
Kuala Lumpur, 9th July - Universiti Malaysia Pahang (UMP) signed a memorandum of agreement (MoA) with Bank Rakyat to help students further their studies to a higher level. Through this strategic alliance, qualified students can apply for i-Education Financing for up to RM1 million with a financing period of up to 20 years at competitive pro